Comparison of Components of Metabolic Syndrome in Androgenic Alopecia versus Healthy Population - Khan, Jauhar Mumtaz; Abbas, Muhammad; Riaz, Ali; Fida, Najma; Ahmad, Manzoor; Malik, Muhammad Omar (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Introduction: Androgenic alopecia (AA) is hair loss in both men and women who are genetically predisposed. AA is associated with increased cardiovascular and metabolic risk, however the studies are controversial. We planned this study to check if metabolic syndrome (MS) was more common in patients of AA Methods: 100 cases of AA and controls were recruited from dermatology department PAF Hospital Faisal Base, Karachi. Only patients with grade III or more in the Hamilton-Norwood classification were enrolled as cases. Only normal and overweight participants were included, obese were excluded. Anthropometrics were taken and blood was withdrawn for metabolic and hormonal parameters. Results: The participants were within the age range of 25-40 years with mean age of cases 32.3±5.2 years, and controls 28.2±4.5 years. Cases were significantly different from controls in height, weight, waist, BMI, SBP, DBP, insulin, HbA1c, HOMA-IR and lipid profile. Testosterone was more in cases as compared to controls (28.21 versus 22.45 nmol/L) and SHBG was decreased in cases. FAI was significantly increased in cases (p=0.01). MS was 39% in cases as compared to 10% in controls. AA patients were split in groups with and without MS. The AA patients with MS had higher BMI, WC, SBP, DBP, Glucose, HDL, insulin, HOMA-IR, testosterone and FAI as compared to AA with no MS. However they had lower SHBG. Conclusion: Metabolic syndrome is more prevalent in people with androgenic alopecia than healthy population. Free androgen index is a good marker for identifying individuals with metabolic syndrome in androgenic alopecia